Leading Indicators of Banking Crises : Was Asia Different? - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper examines episodes of the banking system distress and crisis in a large sample of countries. The empirical results identify several macroeconomic and financial variables as useful leading indicators. The main macroeconomic indicators were of limited value in predicting the Asian crises; the best warning signs were proxies for the vulnerability of the banking and corporate sector. Full-blown banking crises are shown to be more associated with external developments, and domestic variables are the main leading indicators of severe but contained banking distress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet